Genomic insight into the divergence and adaptive potential of a forgotten landrace G. hirsutum L. purpurascens. (20th June 2021) - Nazir, Mian Faisal; He, Shoupu; Ahmed, Haris; Sarfraz, Zareen; Jia, Yinhua; Li, Hongge; Sun, Gaofei; Iqbal, Muhammad Shahid; Pan, Zhaoe; Du, Xiongming
Abstract: Wild progenitors are an excellent source for strengthening the genetic basis and accumulation of desirable variation lost because of directional selection and adaptation in modern cultivars. Here, we re-evaluate a landrace of Gossypium hirsutum, formerly known as Gossypium purpurascens. Our study seeks to understand the genomic structure, variation, and breeding potential of this landrace, providing potential insights into the biogeographic history and genomic changes likely associated with domestication. A core set of accessions, including current varieties, obsolete accessions, G. purpurascens, and other geographical landraces, are subjected to genotyping along with multilocation phenotyping. Population fixation statistics suggests a marked differentiation between G. purpurascens and three other groups, emphasizing the divergent genomic behavior of G. purpurascens . Phylogenetic analysis establishes the primitive nature of G. purpurascens, identifying it as a vital source of functional variation, the inclusion of which in the upland cotton (cultivated G. hirsutum ) gene pool may broaden the genetic basis of modern cultivars. Genome-wide association results indicate multiple loci associated with domestication regions corresponding to flowering and fiber quality. Moreover, the conserved nature of G. purpurascens can also provide insights into the evolutionary process of G. hirsutum .